Legalitas Akad Nikah Daring dalam Perspektif Fikih Islam Kontemporer: Reinterpretasi Ittihād al-Majlis di Era Digital - Khusnul Khotimah; Luluk Afifah; Lutfi Maisaroh; Rizkon Jaya (Bulletin of Indonesian Islamic Studies, 2023)
The development of digital technology has transformed the practice of marriage contracts, particularly with the rise of online marriage contracts increasingly prevalent since the COVID-19 pandemic. In Islam, the marriage contract is a form of worship that must meet specific conditions, including the execution of offer and acceptance (ʾijāb and qabūl) within one assembly (ittihād al-majlis). This study aims to examine the legality of online marriage contracts from the perspective of contemporary Islamic jurisprudence, focusing on the reinterpretation of the concept of ittihād al-majlis in the digital era. The research employs a qualitative literature review method, analyzing the views of classical and modern scholars such as Imam al-Shafi’i, Wahbah al-Zuhaili, and Yusuf al-Qaradawi. The findings indicate that online marriage contracts can be deemed valid if they fulfill the pillars and conditions of marriage, including the occurrence of ʾijāb and qabūl directly and simultaneously through real-time digital communication. The reinterpretation of ittihād al-majlis allows Islamic law to adapt to technological advancements without compromising the objectives of Shariah (maqāṣid al-sharī‘ah). This study contributes to the renewal of Islamic law that is responsive to changing times, while emphasizing the need for clear legal guidelines from religious authorities to ensure the validity of online marriage contracts. Thus, online marriage contracts can offer a practical solution that aligns with Shariah principles and the social needs of modern Muslim communities.